A low dose of RBD and TLR7/8 agonist displayed on influenza virosome particles protects rhesus macaque against SARS-CoV-2 challenge - Gerrit Koopman; Mario Amacker; Toon Stegmann; Ernst J. Verschoor; Babs E. Verstrepen; Farien Bhoelan; Denzel Bemelman; Kinga P. Böszörményi; Zahra Fagrouch; Gwendoline Kiemenyi-Kayere; Daniella Mortier; Dagmar E. Verel; et al. (Scientific Reports, 2023)
Abstract Influenza virosomes serve as antigen delivery vehicles and pre-existing immunity toward influenza improves the immune responses toward antigens. Here, vaccine efficacy was evaluated in non-human primates with a COVID-19 virosome-based vaccine containing a low dose of RBD protein (15 µg) and the adjuvant 3M-052 (1 µg), displayed together on virosomes. Vaccinated animals (n = 6) received two intramuscular administrations at week 0 and 4 and challenged with SARS-CoV-2 at week 8, together with unvaccinated control animals (n = 4). The vaccine was safe and well tolerated and serum RBD IgG antibodies were induced in all animals and in the nasal washes and bronchoalveolar lavages in the three youngest animals. All control animals became strongly sgRNA positive in BAL, while all vaccinated animals were protected, although the oldest vaccinated animal (V1) was transiently weakly positive. The three youngest animals had also no detectable sgRNA in nasal wash and throat. Cross-strain serum neutralizing antibodies toward Wuhan-like, Alpha, Beta, and Delta viruses were observed in animals with the highest serum titers. Pro-inflammatory cytokines IL-8, CXCL-10 and IL-6 were increased in BALs of infected control animals but not in vaccinated animals. Virosomes-RBD/3M-052 prevented severe SARS-CoV-2, as shown by a lower total lung inflammatory pathology score than control animals.